You are awesome - Syed, Matthew (Sourcebooks Explore, 2019)
Encourages children to recognize the limitations they place on themselves and encourages them to overcome personal challenges and self-imposed barriers to success. Provides tips and strategies for achieving one's goals--being awesome--and debunks various myths about success by highlighting notable people who achieved great things that run contrary to these myths.